Downstream Toward Home : A Book of Rivers - Houck, Oliver A. (Book collections on Project MUSE., 2014)
Rivers have played a remarkable role throughout our national history. The outcome of battles, the fate of pioneers, and the survival of early settlers were inextricable from the course and temperament of surrounding rivers. Depicted in songs, art, and fiction, these waterways found a place in the American psyche and continue to wind through the imaginations of modern adventurers. In Downstream Toward Home, Oliver A. Houck recounts his thrilling, meditative, and humorous experi-ences on these oft-neglected tributaries and streams. Spanning more than sixty years and exploring more than thirty-two.